2018
DOI: 10.1039/c7cp07922b
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent presence of on- and off-pathway folding intermediates of apoflavodoxin at physiological ionic strength

Abstract: Flavodoxins have a protein topology that can be traced back to the universal ancestor of the three kingdoms of life. Proteins with this type of architecture tend to temporarily misfold during unassisted folding to their native state and form intermediates. Several of these intermediate species are molten globules (MGs), which are characterized by a substantial amount of secondary structure, yet without the tertiary side-chain packing of natively folded proteins. An off-pathway MG is formed at physiological ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…In most protein folding reactions, intermediates are seen to form very rapidly, usually forming too fast to measure. 12,19,24,29,39,69,[73][74][75][76][77][78] Consequently, U and I are effectively at equilibrium before further folding occurs, and it becomes very difficult to establish whether I is on the direct pathway from U to N or whether it is a nonproductive side-product that has to unfold back to U for folding to proceed to N. [26][27][28] In the current study, I is seen to form slowly enough for the rate constants of its formation and disappearance to be precisely determined. The individual rate constants for the formation of N, from I on one pathway and from C on the other pathway (Scheme 1), are about the same (Figures 2 and 3; Table 1) and hence, equal to the net rate constant for the formation of N. The observation that the rate constant of the disappearance of I is the same as the rate constant of the formation of N, is very strongly supportive of I being a productive on-pathway intermediate (Table 1).…”
Section: Mechanism Of Folding Of Dcmnmentioning
confidence: 70%
“…In most protein folding reactions, intermediates are seen to form very rapidly, usually forming too fast to measure. 12,19,24,29,39,69,[73][74][75][76][77][78] Consequently, U and I are effectively at equilibrium before further folding occurs, and it becomes very difficult to establish whether I is on the direct pathway from U to N or whether it is a nonproductive side-product that has to unfold back to U for folding to proceed to N. [26][27][28] In the current study, I is seen to form slowly enough for the rate constants of its formation and disappearance to be precisely determined. The individual rate constants for the formation of N, from I on one pathway and from C on the other pathway (Scheme 1), are about the same (Figures 2 and 3; Table 1) and hence, equal to the net rate constant for the formation of N. The observation that the rate constant of the disappearance of I is the same as the rate constant of the formation of N, is very strongly supportive of I being a productive on-pathway intermediate (Table 1).…”
Section: Mechanism Of Folding Of Dcmnmentioning
confidence: 70%
“…Two-state models also break down when two phase boundaries lie close to one another (top left in Figure B), and multiple states can coexist. Such “third states” can lie on the pathway for folding, or they can act as traps that hinder refolding because the protein must unfold again before resampling configurations to finally fold. , …”
Section: Phase Diagrams Of Proteinsmentioning
confidence: 99%
“…Such "third states" can lie on the pathway for folding, 29−31 or they can act as traps that hinder refolding because the protein must unfold again before resampling configurations to finally fold. 32,33 Protein−protein surface interactions are in many ways analogous to folding: they are still driven by matching of hydrophobic surfaces, even though polar and electrostatic interactions also play a role, 34 and just as folding often produces marginally stable native states to preserve functionally useful fluctuations, protein−protein interactions are not necessarily optimal for function when they are strongest. Strong binding and having many binding partners are mutually exclusive due to the limited information capacity of a protein surface to encode such interactions.…”
Section: Phase Diagrams Of Proteinsmentioning
confidence: 99%
“…Previous bulk studies have investigated the role of cofactor binding on the folding of flavoproteins that contain the cofactor flavin mononucleotide (FMN). These studies showed that flavoproteins can form molten globules or fold into their native state independently of the cofactor [11][12][13] or fold into an intermediate that is stabilized by FMN binding before reaching the native state 14 . More recently, single molecule manipulation methods have enabled the direct kinetic characterization of intermediates along the folding pathway of small, single-domain proteins that have metal cofactors [15][16][17][18][19] However, these methods have not been applied to proteins that bind to flavin cofactors, let alone multi-domain proteins that bind one of the most common large cofactors known, flavin adenosine diphosphate (FAD).…”
Section: Introductionmentioning
confidence: 99%